Presentation Andean Religiosity (No. 31) - Romero, Catalina (1988)
Religion in Peru has proven to be a field of action and dynamic symbolic creativity and in interaction and dynamic symbolic creativity and in interaction with other fields of social and political life in the country. A fundamental component of culture, it has the force of a natural phenomenon when it mobilizes entire communities in a common sense of solidarity and commitment to life. As a component of the social and cultural identity of a large and ethnically complex people, it expresses itself in very diverse ways and runs through institutional channels that stem from two historical traditions that are sometimes in conflict, sometimes integrated and, why not say so, creating new synthesis, if we speak in general of the Peruvian experience, between the autochthonous Andean tradition and the Hispanic, Western or Catholic tradition.